DYSLIPIDEMIA IS A MAJOR FACTOR IN STEM CELL DAMAGE INDUCED BY UNCONTROLLED LONG-TERM TYPE 2 DIABETES AND OBESITY IN THE RAT, AS SUGGESTED BY THE EFFECTS ON STEM CELL CULTURE - Masouminia, M (J Sex Med, 2018)
BACKGROUND. Previous work showed that muscle derived stem cells (MDSC) exposed long-term to the milieu of uncontrolled type 2 diabetes (UC-T2D) in male obese Zucker (OZ) rats, were unable to correct the associated erectile dysfunction and the underlying histopathology when implanted into the corpora cavernosa, and were also imprinted with a noxious gene global transcriptional signature (gene-GTS), suggesting that this may interfere with their use as autografts in stem cell therapy. AIM. To ascertain the respective contributions of dyslipidemia and hyperglycemia to this MDSC damage, clarify its mechanism, and design a bioassay to identify the damaged stem cells. METHODS. Early diabetes (ED)-MDSC and late diabetes (LD)-MDSC were respectively isolated from nearly normal young OZ rats, and moderately hyperglycemic and severely dyslipidemic/obese aged rats with erectile dysfunction. Monolayer cultures of ED-MDSC were incubated 4 days in DMEM/10% fetal calf serum + or - aged OZ or LZ serum from non-diabetic lean Zucker rats (0.5–5%) or with soluble palmitic acid (PA) (0.5–2 mM), cholesterol (CHOL) (50–400 mg/dl), or glucose (10–25 mM). OUTCOMES. Fat infiltration was estimated by Oil red O, apoptosis by TUNEL, protein expression by western blots, and gene-GTS and microRNA (miR)-GTS were determined in these stem cells RNA. RESULTS. Aged OZ serum caused fat infiltration, apoptosis, myostatin overexpression, and impaired differentiation. Some of these changes, and also proliferation decrease occurred with PA and CHOL. The gene-GTS changes by OZ serum did not resemble the in vivo changes, but some occurred with PA and CHOL. The miR-GTS changes by OZ serum, PA, and CHOL resembled most of the in vivo changes. Hyperglycemia did not replicate most alterations. CLINICAL IMPLICATIONS. MDSC may be damaged in long-term UC-T2D/obese patients and be ineffective in autologous human stem cell therapy, that may be prevented by excluding the damaged MDSC. STRENGTHS AND LIMITATIONS. The in vitro test of MDSC is innovative and fast to define dyslipidemic factors inducing stem cell damage, its mechanism, prevention and counteraction. Confirmation is required in other T2D/obesity rat models and stem cells (including human), as well as miR-GTS biomarker validation as stem cell damage biomarker. CONCLUSION. Serum from long-term UC-T2D/obese rats or dyslipidemic factors induce a noxious phenotype and miR-GTS on normal MDSC, that may lead in vivo to the repair inefficacy of LD-MDSC. This suggests that autograft therapy with MDSC in long-term UT-T2D obese patients may be ineffective, albeit this may be predictable by prior stem cell miR-GTS tests.